Raymundo Moraes na planície do esquecimento - LARÊDO, Salomão (2007)
Raymundo Moraes (1872 - 1941), was a Brazilian writer, that was born in Para (Stated located in the North of Brazil), he wrote seventeen works in that the literary universe was the Amazon, he obtained for his book entitled "Na Planície Amazônica" (= In the Amazon Plain), among other, the praise done by Washington Luís (Brazilian Republic President in the thirties) - that used this book to know the area, and soon after the work obtained national repercussion with the author enjoy of fame and critical fortune that later took it, paradoxically, to complete forgetfulness: his name not more it was pronounced, also not pronounce of the Common Justice for the imputed crime - homicide. This dissertation has for main objective to call the academic community's attention and of the reader in general for the importance of the literary work of this paraense writer, today, unknown, autodidactic, commandant of ships for the rivers of the area, journalist, political, member of intellectual activities of his time, besides member of linked entities to the Belles letters. It went to the literary podium in the decade of 1930 and later it lowered to the catacombs of the unawareness, deserving to be represented and recognized in a homage of gratitude and justice, due to his considerable production regarding the Amazonian, because many of his works, as "Meu dicionário de Cousas da Amazônia" (= My dictionary of Amazonian things), written in 1931, continue being source of indispensable investigation for the ones that dedicated to study regarding the Amazon Area and its culture(s), as well as they fed the Mário de Andrade's anthropophagous voracity.